2017
DOI: 10.1002/mc.22681
|View full text |Cite
|
Sign up to set email alerts
|

BMP4 enhances hepatocellular carcinoma proliferation by promoting cell cycle progression via ID2/CDKN1B signaling

Abstract: Bone morphogenetic protein-4 (BMP4) plays a crucial role in carcinogenesis, but the effects and signaling mechanisms of BMP4 in hepatocellular carcinoma (HCC) are not clearly clarified. The present study aimed to identify the roles of BMP4 in the proliferation of human HCC. In this study, BMP4 expression and its correlation with clinicopathological characteristics and the survival of HCC patients were analyzed in two independent cohorts consisting of 310 subjects. Functional analysis of BMP4 on HCC proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…In our previous study, we have previously testified that application of BMP4 recombinant protein could enhance the proliferation of HCC cells Bel-7402 and HCCLM3 by promoting cell cycle via ID2/CDKN1B signaling [ 14 ]. But the effects of BMP4 on autophagy-regulated HCC growth remain unknown.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we have previously testified that application of BMP4 recombinant protein could enhance the proliferation of HCC cells Bel-7402 and HCCLM3 by promoting cell cycle via ID2/CDKN1B signaling [ 14 ]. But the effects of BMP4 on autophagy-regulated HCC growth remain unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have identified BMP4 as an onco-protein with frequent overexpression in tumor tissues and positive regulation of proliferation, chemo-resistance and metastasis in several cancer cells such as the breast [ 22 ], ovarian [ 23 ], pancreatic [ 24 ], gastric [ 15 ] and colon [ 25 ] cancers. Our previous studies have found that BMP4 acted as a tumor promotion protein by facilitating HCC proliferation, invasion and chemoresistance, as well as identified its prognostic value in HCC patients [ 13 , 14 , 26 ]. Herein, we investigated the role of BMP4 on autophagy-regulated HCC proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Epithelial-to-mesenchymal transition (EMT) is a significant molecular mechanism in the steps of distant metastasis by suppression of epithelial markers, up-regulation of mesenchymal markers. 5,6 EMT promotes cancer cells switching a polarized epithelium to a highly invasive mesenchymal phenotype, and it requires a succession of complicated cellular events including the loss of polarity and tight junctions, desmosomes and cytokeratin intermediate filaments, and the alteration in cytoskeletal architecture through the modulation of EMT-related factors. 7,8 EMT is considered as a crucial event in cancer metastasis, and many factors can induce or mediate EMT.…”
Section: Introductionmentioning
confidence: 99%
“…Both BMP4 (bone morphogenetic protein 4) and NODAL encode ligand of the TGF-b superfamily. Recent studies revealed that BMP4 could enhance HCC proliferation and metastasis (Ma et al 2017;Zeng et al 2017) and is associated with poor prognosis in HCC samples (Guo et al 2012). Over-expression of NODAL is involved in promoting invasive phenotypes of tumor cells in vitro (Duan et al 2015;Quail et al 2014).…”
Section: Difference Of Immune-related Genes By Subtypementioning
confidence: 99%